Caffeinated chewing gum produces comparable strength and power gains to capsules with fewer side effects in resistance-trained men - Li Ding; Jue Liu; Yixuan Ma; Litian Bai; Li Guo; Bin Chen; Yinhang Cao; Olivier Girard (Journal of the International Society of Sports Nutrition, 2025)
Background Caffeine, widely used as an ergogenic aid, has been extensively studied regarding its dosage and timing of ingestion. However, the impact of different administration methods on caffeine’s performance-enhancing effects remains relatively underexplored. This study compared the effects of caffeine administered via chewing gum versus capsules on maximal strength, muscular power, and side effects during bench press and back squat exercises.Methods Sixteen resistance-trained males participated in a double-blind, randomized trial, ingesting either a 4 mg/kg caffeine capsule (CC) or placebo capsule (PC) one hour before testing, or a 4 mg/kg caffeinated gum (CG) (4 mg/kg) or placebo gum (PG) five minutes prior. Assessments including one-repetition maximum (1RM) and muscular power at 25%, 50%, 75%, and 90%1RM for bench press and back squat.Results Caffeine increased 1RM (+2.1–5.0%) and muscular power (+6.1–20.0%) in both the bench press and back squat compared to placebo (all p < 0.05). However, no significant differences were observed between CC and CG for maximal strength or muscular power (all p > 0.05). Furthermore, CG was associated with fewer reports of gastrointestinal discomfort (12.5% vs. 37.5%) immediately post-exercise and tachycardia/heart palpitations (0% vs. 25.0%) at 24 hours compared to CC (all p < 0.05).Conclusion Caffeinated gum (4 mg/kg) produced ergogenic effects comparable to capsules in enhancing maximal strength and muscular power during bench press and back squat exercises, with fewer side effects in resistance-trained men.